Konsentrasi dan Energi Urbach Nanopartikel ZnO yang Disintesis Menggunakan Enkapsulan Tween 80 - Saragih, Horasdia; Yustian , William; Lingga , Ananda E.J.; Simanjuntak , Anggraini O.; Marcia, Brianna D.; Manalu, Dea R.; Oumaro , Gefriella B.; Leo, Jeanet G.R.; Kusminarti , Karin; Silalahi, Ladyos D.; La'lang , Michelle A.; Nurbayanti , Rima S.; Leo , Ruly Y.R.R.; Situmorang , Santika; Siahaan , Widya A. (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Excessive exposure to ultraviolet (UV) radiation can cause skin damage, necessitating the development of effective and transparent sunscreen materials. ZnO nanoparticles are a promising candidate; however, they often suffer from agglomeration, which degrades their optical performance. This study aims to investigate the effect of varying concentrations of Tween 80 as an encapsulating agent on the optical and structural characteristics of ZnO nanoparticles. The nanoparticles were synthesized using a rotor–stator homogenization method with Tween 80 concentrations ranging from 2 to 5 mL (each dissolved in 50 mL of ethanol), followed by characterization using UV–Vis spectroscopy. The results indicate that increasing the concentration of Tween 80 enhances the concentration of ZnO nanoparticles without significantly altering the average particle size ( 2.44 nm), resulting in a monodisperse system. Urbach energy analysis reveals that crystal order improves up to an optimum at 4 mL of Tween 80, followed by a slight decrease at higher concentrations. Optically, all samples exhibit strong absorption in the UV region and high transmittance in the visible range (95–100%). These findings demonstrate that the synthesized ZnO nanoparticles have strong potential as a sunscreen. It is concluded that Tween 80 plays a crucial role in controlling the growth, crystal structure, and optical properties of ZnO nanoparticles, with the optimum concentration yielding the best performance.